Analisis Usability Pada Website Universitas Xyz Palembang - Adrima, M. Rizky; Novita, Dien; Oktaviany, Della (Universitas Lembah Dempo, 2019)
XYZ University Palembang is an education institute that using internet during academic process has 5 faculty. In this study, there was still weaknesses from the website; the website could not measure the level of user satisfaction, user could not interact with website and the University could not know how well the use of the website. With those problems, user satisfaction measurement usability analysis in XYZ University Palembang had to do in order to know how great user satisfaction in interaction with website. AMOS, SPSS, and SEM Analysis technique was used in website measurement usability. The result of this study had not reach the 5 aspects of usability, it was proven based on the measurement that the factor of content has more than 50% contribution, while the ease of use, customization, and download delay was less than 50%. So it is worth saying that the user was notsatisfaction.